The Ottoman Middle East : studies in honor of Amnon Cohen - Cohen, Amnon, 1936-; Ginio, Eyal.; Podeh, Elie.; Milstein, Rachel. (The Ottoman Empire and its Heritage, 2014)
This collection of articles discusses various political, social, cultural and economic aspects of the Ottoman Middle East. By using various textual and visual documents, produced in the Ottoman Empire, the collection offers new insights into the matrix of life during the long period of Ottoman rule. The different parts of the volume explore the main topics studied by Amnon Cohen: Ottoman Palestine, Egypt and the Fertile Crescent under Ottoman rule, Ottoman Jews and their relations with the surrounding societies and various social aspects of Ottoman societies.